Recent Advances in Ruddlesden–Popper Phase-Layered Perovskite Sr2TiO4 Photocatalysts - Pei Wang; Lijun Liao; Hongqi Chu; Ying Xie; Zhenzi Li; Wei Zhou (Nanomaterials)
Sr2TiO4, a prominent member of the Ruddlesden–Popper (RP) perovskite family, has garnered significant interest in photocatalysis, primarily owing to its distinctive two-dimensional (2D) layered structure. In this review, we provide an insightful and concise summary of the intrinsic properties of Sr2TiO4, focusing on the electronic, optical, and structural characteristics that render it a promising candidate for photocatalytic applications. Moreover, we delve into the innovative strategies that have been developed to optimize the structural attributes of Sr2TiO4. These strategies aim to maximize light absorption, improve charge separation, and accelerate the photocatalytic reaction rates. By highlighting these unique approaches, we strive to contribute to a more profound understanding of the material’s potential and stimulate further advancements in developing Sr2TiO4-based photocatalytic systems. The review not only synthesizes the existing knowledge but also offers a perspective in future directions for research and application. As the field of photocatalysis continues to evolve, Sr2TiO4 stands poised to play a pivotal role in the quest for more efficient and sustainable solar energy conversion technology.